Britain alone : how a decade of conflict remade the nation - Stanley, Liam (Manchester University Press, 2022)
Ten years after it was initiated, this book provides the definitive account of the 'age of austerity' from high politics to everyday life and how it is permanently altering British society. It shows how scarcity in the name of national survival is intensifying social conflict over who gets what, when, and how.